Lung Alveolar Repair: Not All Cells Are Equal - Dean,CH; Lloyd,CM (TRENDS IN MOLECULAR MEDICINE, 2017)
The lungs are capable of repair but the extent to which this occurs varies widely. Recent data indicate that, following injury, different progenitor cell populations can arise, depending on the molecular environment. In turn, these result in either normal or aberrant alveolar repair. Thus, a key question in lung regenerative medicine is how to maintain a ‘Goldilocks zone’ of repair.